THU0058 Periodontal disease is associated with rheumatoid arthritis (RA) but its severity is not correlated with RA disease activity. (23rd January 2014) - Choi, I.A.; Kim, J.-H.; Kim, Y.M.; Kim, K.H.; Kim, H.W.; Shin, K.; Lee, E.Y.; Lee, E.B.; Lee, Y.-M.; Song, Y.W.
Abstract : Background: The prevalence of periodontal disease is known to be increased in patients with rheumatoid arthritis (RA) compared to the general population. Patients with RA have diverse risk factors of periodontal disease such as use of steroid and immunosuppressant, disability with tooth-brushing in advanced disease and secondary Sjogren's syndrome. Objectives: We investigated whether periodontal disease is associated with RA and whether severity of periodontal disease is correlated with RA disease activity, ACPA status or treatment medication. Methods: We investigated 290 RA patients and 49 healthy controls. Clinical parameters including tender joint count (TJC), swollen joint count (SJC), DAS28 and presence of erosive changes in X- ray were evaluated at the time point obtaining the samples. Serum RF, anti-CCP antibody, CRP and ESR levels were measured. A number of teeth (0∼28, 3rd molars excluded) was checked. Subjects who had 15 or more teeth were evaluated for dental exam. Plaque index (PI, scale of 0, 1, 2, 3) was evaluated as a marker of dental hygiene and gingival index (GI, scale of 0, 1, 2, 3), probing pocket depth (PPD, 1-12 mm scale), bleeding on probing (BOP, 1 or 0) and clinical attachment loss (CAL, PPD [mm]+gingival recession [mm]) were evaluated as index of periodontitis. Periodontitis was defined as mild (CAL 1∼2 mm), moderate (CAL 3∼4 mm) and severe (CAL ≥5mm) by American Academy of Periodontology 2004 Classification. Results: The mean number of teeth (±SD) in 290 RA patients and 49 healthy controls were 23.2±6.8 vs. 26.0±3.8, respectively ( p = 0.006 ). Among 290 RA patients, 27 patients (9.3%) had less than 15 teeth and 3 patients had ongoing dental care, both were excluded from the dental exam. One person (2%) had 6 teeth among 49 healthy controls ( p=0.1 ). Mean PI in 260 RA patients and 48 healthy controls were 0.84±0.49 and 0.64±0.31 (p=0.006), mean GI 0.51±0.43 vs. 0.17±0.18 ( p = 0.000 ), mean PPD 1.96±0.36 vs. 1.79±0.22 ( p = 0.002 ), mean BOP 20.25±15.43 vs. 12.79±10.11 ( p = 0.001 ) and mean CAL 3.23±0.77 vs. 2.94±0.49 ( p = 0.014 ). The prevalence of moderate or severe periodontitis was significantly higher in RA patients compared to healthy controls (63.5% vs. 39.5%, p=0.002 ). In RA patients, smoking was associated with higher PI (r=0.128, p=0.040 ), PPD (r=0.129, p=0.037) and CAL (r=0.203, p=0.001). Presence of diabetes was associated with higher PI (r=0.145, p=0.019 ) and GI (r=0.182, p=0.003). Dry mouth was associated with higher BOP (r=0.148, p=0.017 ). Disease duration was associated with higher GI (r=0.193, p=0.002 ) and BOP (r=0.147, p=0.017 ). There was no significant association between severity of periodontitis and RA disease activity markers (TJC, SJC, ESR, CRP, DAS28), presence of bone erosion, rheumatoid factor, anti-CCP antibody or use of steroid or biologic agent. Conclusions: Patients with RA had more severe periodontitis index than healthy controls. Severity of periodontitis was associated with RA disease duration but not with disease activity. Disclosure of Interest: None Declared